A multicenter, randomized, controlled trial on short-term feasibility and impact on functional capacity, symptoms and neurohumoral activation - Mezzani, Alessandro; Cacciatore, Francesco; Catanzaro, Raffaella; Gualco, Alessandra; Guzzetti, Daniela; Leosco, Dario; Monelli, Mauro; Tarro Genta, Franco; Totaro, Paolo; Traversi, Egidio; Zanelli, Emanuela; Giannuzzi, Pantaleo (Monaldi Archives for Chest Disease, 2015)
RE-START is a multicenter, randomized, prospective, open, controlled trial aiming to evaluate the feasibility and the short- and medium-term effects of an earlystart AET program on functional capacity, symptoms and neurohormonal activation in chronic heart failure (CHF) patients with recent acute hemodynamic decompensation. Study endpoints will be: 1) safety of and compliance to AET; 2) effects of AET on i) functional capacity, ii) patient- reported symptoms and iii) AET-induced changes in beta-adrenergic receptor signaling and circulating angiogenetic and inflammatory markers. Two-hundred patients, randomized 1:1 to training (TR) or control (C), will be enrolled. Inclusion criteria: 1) history of systolic CHF for at least 6 months, with ongoing acute decompensation with need of intravenous diuretic and/or vasodilator therapy; 2) proBNP >1000 pg/ml at admission. Exclusion criteria: 1) ongoing cardiogenic shock; 2) need of intravenous inotropic therapy; 3) creatinine >2.5 mg/dl at admission. After a 72-hour run-in period, TR will undergo the following 12-day early-start AET protocol: days 1-2: active/passive mobilization (2 sessions/day, each 30 minutes duration); days 3-4: as days 1-2 + unloaded bedside cycle ergometer (3 sessions/day, each 5-10 minutes duration); days 5-8: as days 1-2 + unloaded bedside cycle ergometer (3 sessions/day, each 15-20 minutes duration); days 9-12: as days 1-2 + bedside cycle ergometer at 10-20 W (3 sessions/day, each 15-20 minutes duration). During the same period, C will undergo the same activity protocol as in days 1-2 for TR. All patients will undergo a 6- minWT at day 1, 6, 12 and 30 and echocardiogram, patient- reported symptoms on 7-point Likert scale and measurement of lymphocyte G protein coupled receptor kinase, VEGF, angiopoietin, TNF alfa, IL-1, IL-6 and eNOS levels at day 1, 12 and 30.